Chiari II Malformation: MR Imaging Evaluation - Wolpert, Samuel M.; Anderson, Mary; Scott, R. Michael; Kwan, Eddie S. K.; Runge, Val M. (American Journal of Neuroradiology, 1987)
The purpose of this study was to explore the value of high-detail MR imaging in the diagnosis of the Chiari II malformation. Twenty-four patients with known Chiari II malformation as diagnosed by CT scanning were evaluated with cranial MR scans. Two patients also had spine scans. The sagittal-plane images were the most informative, and abnormalities of the telencephalon, diencephalon, mesencephalon, rhomboencephalon, upper spinal cord, and mesencephalon were shown extremely well. We found MR to be an easy and accurate method for demonstrating the abnormalities of the Chiari II malformation, and it is our procedure of choice.